2014
DOI: 10.1007/s00441-014-1983-9
|View full text |Cite
|
Sign up to set email alerts
|

The vertebrate homologue of sulfide-quinone reductase in mammalian mitochondria

Abstract: Hydrogen sulfide (H2S) is the first inorganic compound identified as both a substrate for mitochondrial oxidative phosphorylation and a transmitter in mammalian cells. H2S seems to mediate effects that are correlated with those of nitric oxide (NO) by a reciprocal regulation. Moreover, H2S is consumed by mitochondrial oxidation mediated by sulfide-quinone reductase-like protein (SQRDL)-the vertebrate homolog of sulfide-quinone oxidoreductase (SQR). There is evidence that SQR plays an essential role in regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…There are a number of mitochondrial processes that could be influenced by H 2 S during cold IRI. As previously described, low levels of H 2 S can stimulate ATP production through donation of electrons to the ETC . In the absence of O 2 and nutrients during ischemia, this action of H 2 S could potentially minimize the detrimental impact of ATP depletion on cellular function and viability.…”
Section: Discussionmentioning
confidence: 84%
“…There are a number of mitochondrial processes that could be influenced by H 2 S during cold IRI. As previously described, low levels of H 2 S can stimulate ATP production through donation of electrons to the ETC . In the absence of O 2 and nutrients during ischemia, this action of H 2 S could potentially minimize the detrimental impact of ATP depletion on cellular function and viability.…”
Section: Discussionmentioning
confidence: 84%
“…This whole process allowing for sulfide to be used as an inorganic substrate for the human electron transfer chain. SQR is a component of several mammalian tissues, and protein expression has been confirmed within heart, lung, colon, liver, kidney, thyroid, brain, leukocytes, and penis and testicles of mice and rats [230]. Fractionation experiments revealed this protein to be localised to mitochondria.…”
Section: Sulfide–quinone Reductase-like Protein Knockout Modelsmentioning
confidence: 99%
“…SQOR proteins with a molecular mass of about 50 kDa, and associated with the prokaryotic cytoplasmic membrane or the mitochondrial inner membrane [28]. SQOR avidly consume sulfide as a fuel in the mitochondria isolated from mouse kidneys, liver, heart and brain [29,30], so it is a key enzyme during the metabolism of H 2 S to maintain the sulfide homeostasis and bioenergetics. SQOR in mitochondrial catalyzes a two-electron oxidation of H 2 S to sulfane sulfur using coenzyme Qas the electron acceptor and the sulfane sulfur produced in the SQOR reaction is a metabolic precursor of substrates for better-characterized down-stream enzymes, such as sulfite oxidase [31].…”
Section: H2s Formation Oxidation Toxicity and Physiological Funmentioning
confidence: 99%
“…Human SQOR can use multiple thiophilic acceptors, including sulfide, sulfite, and glutathione, to form as products, hydrodisulfide, thiosulfate, and glutathione persulfide, respectively [32]. Moreover, H 2 S is also consumed by mitochondrial oxidation mediated by sulfide quinone reductase-like protein (SQRDL)-the vertebrate homolog of SQOR [29,30]. Jin et al found that overexpression of the SQRDL I264T variant in the preosteoblast MC3T3-E1 cells significantly increased osteogenic differentiation and mineralization, whereas the SQRDL wild type had no effect or a negative effect on osteoblast differentiation.…”
Section: H2s Formation Oxidation Toxicity and Physiological Funmentioning
confidence: 99%